Economic and Accounting Aspects of Strategic Management - Ahmed, Mariyam; Pandey, ShinkiKatyayani (International Journal of Accounting and Economics Studies, 2025)
Despite extensive planning efforts, India’s economic policy’s industrialization strategy—which included giving surplus laborers gainful employment, reducing poverty, and distributing wealth and income equally—was unable to be implemented. There’s been a noticeable shift away from the once-celebrated benefits of large-scale economic units, bringing the spotlight back to "Small Business." Recent research has underscored just how vital management accounting is for driving organizational success. Over time, the demand for a deeper understanding of strategic management accounting has only intensified, reflecting its growing importance. Considering this, our study employed a qualitative approach, including a thorough accounting foundation of strategic management, the various contingency factors at play, and their effects on organizational performance. We’re highlighting some important ways to improve this theoretical framework, with the goal of giving practitioners useful insights. These insights can help them better align their strategic management accounting practices to achieve the best outcomes for their organizations, all grounded in the data we’ve analysed. We’ve also acknowledged the limitations of this study.